2009
DOI: 10.1530/eje-09-0222
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of GH deficiency in cured acromegalic patients: impact of different previous treatments

Abstract: Objective: Radiotherapy (RT) for pituitary adenomas, including GH-secreting ones, frequently leads to GH deficiency (GHD). Data on the effects of surgery alone (S) on dynamic GH secretion are limited. The aim of the study was to investigate the occurrence of GHD in acromegalic patients treated with different therapeutic options. Design and methods: Fifty-six patients in remission from acromegaly, (33 F & 23 M, age: 54G13 years, body mass index (BMI): 28.4G4.1 kg/m 2 , 21 with adequately substituted pituitary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
(20 reference statements)
2
27
4
Order By: Relevance
“…In contrast, our study is the first report demonstrating the frequency of sGHD evaluated by GHRP2 or GHRP2 plus arginine tests in a large number of cured patients fulfilling more stringent new criteria for cure of acromegaly. Compared with the report by Ronchi et al (9), sGHD was less common in our patients and was found only in 17 (9.1%) of the 186 patients. This lower percentage of sGHD in our patients may be due to different methods to evaluate sGHD.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…In contrast, our study is the first report demonstrating the frequency of sGHD evaluated by GHRP2 or GHRP2 plus arginine tests in a large number of cured patients fulfilling more stringent new criteria for cure of acromegaly. Compared with the report by Ronchi et al (9), sGHD was less common in our patients and was found only in 17 (9.1%) of the 186 patients. This lower percentage of sGHD in our patients may be due to different methods to evaluate sGHD.…”
Section: Discussioncontrasting
confidence: 92%
“…Ronchi et al (9) first revealed the rate of sGHD after surgery as 54.5% in a relatively large number of patients (33 patients) by GHRH plus arginine tests. Those 33 patients were judged as cured based on the Cortina consensus criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transsphenoidal surgery is the treatment of choice for intrasellar microadenomas, noninvasive macroadenomas, and when the tumor is causing compression symptoms on the surrounding tissues (4,5). Surgery or radiotherapy as treatment modalities may be burdened by a great prevalence of pituitary hormone deficiencies, including GH deficiency (GHD) (6). Ronchi et al (6) stated that the prevalence of severe GHD is 60% in patients treated for acromegaly by surgery alone or surgery followed by radiotherapy.…”
Section: Introductionmentioning
confidence: 99%